Neglected zoonotic helminthiases in wild canids: new insights from South America - Uribe, Manuel; Brabec, Jan; Chaparro-Gutiérrez, Jenny J.; Hermosilla, Carlos (Frontiers in Veterinary Science, 2023)
The global threat of neglected tropical diseases (NTD) constitutes a public health issue in underdeveloped countries. Zoonotic helminthiases are the most common NTD agents of humans in developing countries of Sub-Saharan Africa, Asia and the Americas thereby causing a global burden of disease exceeding better-known infective illnesses such as malaria and tuberculosis. Wild canids are well-known carnivore mammals to that act as natural reservoirs of zoonotic-relevant helminthiasis worldwide, thus playing a pivotal role in the epidemiology and transmission to humans. Herein, we evaluate the occurrence of zoonotic gastrointestinal helminths in two Neotropical wild canid species of the Amazonian-and Andean regions of Colombia, i. e. the bush dog (Speothos venaticus) and the crab-eating fox (Cerdocyon thous). We recovered tapeworm proglottids from bush dog faecal samples and identified them molecularly as the canine-specific lineage of Dipylidium caninum by using cytochrome c oxidase subunit I (cox1) gene sequences. Moreover, the examination of deceased a crabeating fox during necropsy showed the presence of non-embryonated eggs of the neglected nematode Lagochilascaris cf. minor, as well as both eggs and gravid proglottids of the cestode, Spirometra mansoni during necropsy. These findings constitute the first report of zoonotic-relevant cestodes, i. e. D. caninum ('canine genotype') and S. mansoni as well as the nematode L. cf. minor in bush dogs and crab-eating foxes acting as final hosts. The occurrence of these zoonotic helminthiasis in wild canid species calls for regular monitoring programs to better understand the epidemiology and transmission routes of neglected dipylidiasis, lagochilascariosis and sparganosis in South America.